2017
DOI: 10.1371/journal.pone.0169682
|View full text |Cite
|
Sign up to set email alerts
|

A Chemogenomic Screen Reveals Novel Snf1p/AMPK Independent Regulators of Acetyl-CoA Carboxylase

Abstract: Acetyl-CoA carboxylase (Acc1p) is a key enzyme in fatty acid biosynthesis and is essential for cell viability. To discover new regulators of its activity, we screened a Saccharomyces cerevisiae deletion library for increased sensitivity to soraphen A, a potent Acc1p inhibitor. The hits identified in the screen (118 hits) were filtered using a chemical-phenotype map to exclude those associated with pleiotropic drug resistance. This enabled the identification of 82 ORFs that are genetic interactors of Acc1p. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…1, d and e ). This is in agreement with a chemical genomic screen which identified the NuA4 subunit mutant eaf7 Δ as hypersensitive to Sor A ( Bozaquel-Morais et al 2017 ). As previous studies have shown that NuA4 inhibits Snf1/AMPK activity ( Lu et al 2011 ), a key regulator of Acc1, we next sought to determine if the reduction in Acc1 activity in eaf1 Δ cells was fully or partially due to increases in Snf1 activity.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…1, d and e ). This is in agreement with a chemical genomic screen which identified the NuA4 subunit mutant eaf7 Δ as hypersensitive to Sor A ( Bozaquel-Morais et al 2017 ). As previous studies have shown that NuA4 inhibits Snf1/AMPK activity ( Lu et al 2011 ), a key regulator of Acc1, we next sought to determine if the reduction in Acc1 activity in eaf1 Δ cells was fully or partially due to increases in Snf1 activity.…”
Section: Resultssupporting
confidence: 89%
“…Acc1 is also inhibited by Soraphen A (Sor A), a compound discovered from Sonrangium cellulosum , a myxobacteria, which was initially used as an antifungal but has branched into similar compounds being used in clinical trials ( Gerth et al 1994 ; Vahlensieck et al 1994 ; Naini et al 2019 ). Sor A is commonly used as an indirect measurement of Acc1 activity as mutants deficient for Acc1 activity are hypersensitive and mutants with enhanced Acc1 activity (such as Snf1 or acc1 S1157A mutants) are resistant to Sor A treatment ( Shirra et al 2001 ; Bozaquel-Morais et al 2017 ; Dacquay et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since our data revealed an unexpected role of the Elongator dependent tRNA modifications in regulating LD dynamics and soraphen A resistance, we investigated whether other tRNA modification mutants might display abnormal LD levels, which were identified in a previous screening for changes in soraphen A resistance [ 33 ]. We assembled a set of mutants defective in most of the known tRNA modifications (excluding essential ones) and classified their soraphen A response.…”
Section: Resultsmentioning
confidence: 99%
“…Antimycin A (ethanol), N-acetylcysteine (water), and lithium chloride (water) were obtained from Sigma-Aldrich. The double mutant ubx4⌬snf1⌬ was generated by crossing a haploid MATa ubx4⌬ strain with a haploid MAT␣ snf1⌬ strain previously generated by our group (62). Strains were genotyped using the following primers: SNF1A (5Ј-TAAGAGTATGGC-ACATCAACAGGTA-3Ј), SNF1D (5Ј-TGTAGTAGGTTGT-ATTTTTGTCGCA-3Ј), UBX4A (5Ј-TAAAACGCTAGATG-CTATTTCTTGC-3Ј), UBX4D (5Ј-GAATACAATATCC-CATTTGATCAGG-3Ј), kanB (5Ј-CTGCAGCGAGGAGCC-GTAAT-3Ј), and kanC3 (5Ј-CCTCGACATCATCTGCCC-AGAT-3Ј).…”
Section: Yeast Strains and Growth Conditionsmentioning
confidence: 99%